Impact of cigarette taxes on smoking prevalence from 2001-2015: A report using the Behavioral and Risk Factor Surveillance Survey (BRFSS) - Sharbaugh, Michael S.; Althouse, Andrew D.; Thoma, Floyd W.; Lee, Joon S.; Figueredo, Vincent M.; Mulukutla, Suresh R. (PloS one, 2018)
To provide an up-to-date analysis on the relationship between excise taxes and the prevalence of cigarette smoking in the United States. Linear mixed-effects models were used to model the relationship between excise taxes and prevalence of cigarette smoking in each state from 2001 through 2015. From 2001 through 2015, increases in state-level excise taxes were associated with declines in prevalence of cigarette smoking. The effect was strongest in young adults (age 18-24) and weakest in low-income individuals (<$25,000). Despite the shrinking pool of current smokers, excise taxes remain a valuable tool in public-health efforts to reduce the prevalence of cigarette smoking. States with high smoking prevalence may find increased excise taxes an effective measure to reduce population smoking prevalence. Since the effect is greatest in young adults, benefits of increased tax would likely accumulate over time by preventing new smokers in the pivotal young-adult years.